Pigeon Pea (Cajanus cajan) as an alternative protein source in broiler feed. Issue 3 (September 2018) - ABD EL-HACK, M.E.; SWELUM, A.A.; ABDEL-LATIF, M.A.; MÁS TORO, D.; ARIF, M.
Abstract : Pigeon pea (PP), Cajanus cajan, is a plant that is cultivated for human food and animal feed. It exists as a wide range of cultivars, and their flexibility for use in animal rearing systems have made PP popular, especially for small-scale farmers. PP is grown widely in India and in parts of Africa and Central America. The main producers of PP in the world are India, Uganda, Tanzania, Kenya, Malawi, Ethiopia, Mozambique, the Dominican Republic, Puerto Rico, the West Indies in the Caribbean and Latin America region, Indonesia and the Philippines and Australia. Analysis has shown that PP contains 17.9-24.3% crude protein (CP) in whole grain, and 21.1-28.1% in split seeds, and high protein genotypes contain 32.5%. Optimal levels of utilisation have been shown to improve broiler performance and may reduce daily feed cost. However, PP contains anti-nutritional factors that negatively affect feed efficiency. The use of processing methods such as fermentation, boiling, milling, soaking, and roasting can minimise any harmful effects and improve its nutritive quality, positively enhancing performance parameters. Studies on the use of PP suggested that it can be included at 7.5% of the diet or as 50% substitution for soybean meal in broiler diets.